Factors influencing the rates of pregnancy, calving and peri-parturient disorders in heifers at selected char areas of Bangladesh (Bangladesh Veterinarian, 2016)
The study was conducted to evaluate the factors affecting the rates of pregnancy, calving and peri-parturient disorders in heifers in selected char areas (low lying flood and erosion-prone areas in or adjacent to major rivers) of Lalmonirhat district of Bangladesh. A total of 101 artificial inseminated (AI) heifers were randomly selected for monitoring rates of pregnancy, calving and peri-parturient disorders with respect to breed of semen, source of semen, breed, age, body weight and body condition score (BCS) of heifers. The overall rates of pregnancy, calving and peri-parturient disorder were 51.5%, 45.5% and 32.6%, respectively. The differences were not significant with respect to the factors evaluated (P>0.05).Bangl. vet. 2015. Vol. 32, No. 2, 65-72